HLA-B*35-restricted CD8 T cell epitopes in the antigen 85 complex of Mycobacterium tuberculosis. - Klein, MR; Smith, S; Hammond, A; Ogg, G; King, A; Vekemans, J; Jaye, A; Lukey, P; McAdam, K (2001)
Few target epitopes have been described for human CD8 T lymphocytes in antigens of Mycobacterium tuberculosis. By use of a reverse immunogenetics approach, 23 motif-bearing peptides of the Ag85 complex were tested for binding to HLA-B*35, one of the common B-types in West Africa. Three 9-mer peptides bound with high affinity to HLA-B*3501 and displayed low dissociation rates of peptide-major histocompatibility complexes (MHCs). IC(50) and half-life values of peptide-MHC class I complexes were in the same range as reported earlier for other immunogenic peptides. Immune responses against peptide Ag85C (aa 204-212) WPTLIGLAM were characterized in detail. Peptide-stimulated effector cells were able to kill macrophages infected with M. tuberculosis or bacille Calmette-Guérin. Peptide-specific CD8 T cells could be visualized by using HLA-B*3501 tetramers and were shown to produce interferon-gamma and tumor necrosis factor-alpha. Together with other published epitopes, these peptides can be used to study more closely the role of CD8 T cells in mycobacterial infection and tuberculosis.